2014
DOI: 10.1093/carcin/bgu110
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 promotes tumour malignancy via increased nuclear translocation of β-catenin and predicts poor outcome in APC-mutated but not in APC-wild-type colorectal cancer

Abstract: MiR-21 has been associated with poor prognosis in colon adenocarcinomas. However, in our preliminary data, the prognostic value of miR-21 levels was observed only in adenomatous polyposis coli (APC)-mutated tumours, not in APC-wild-type tumours. We explored whether β-catenin nuclear translocation was synergistically promoted by miR-21 in APC-mutated cells but not in APC-wild-type cells. We enrolled 165 colorectal tumour to determine APC mutation, miR-21 levels and nuclear β-catenin expression by direct sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 40 publications
3
29
0
Order By: Relevance
“…These results are consistent with the in vitro experiments reported by Lin et al [25] who demonstrated that over-expressed miR-21-5p (opposite arm of the miR-21-3p) in colorectal cancer cell lines promoted β-catenin nuclear translocation via increased phosphorylation of this protein at Serine552 and this phenomenon was associated with mutated CTNNB1 gene.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with the in vitro experiments reported by Lin et al [25] who demonstrated that over-expressed miR-21-5p (opposite arm of the miR-21-3p) in colorectal cancer cell lines promoted β-catenin nuclear translocation via increased phosphorylation of this protein at Serine552 and this phenomenon was associated with mutated CTNNB1 gene.…”
Section: Discussionsupporting
confidence: 93%
“…The translocation of β-catenin is a key molecular event in tumor formation [19]. In colorectal cancer, due to a mutation in the APC tumor suppressor gene, β-catenin accumulates and translocates into the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al [3] is involved in the development of malignant tumors through its effects on cell apoptosis, proliferation, invasion, and metastasis by targeting phosphatase, tensin homolog (PTEN), and tissue inhibitor of metalloproteinases 3 (TIMP3) or through its role in signaling pathways such as Wnt/β-catenin, PTEN/PI-3K/AKT, and RAS/ MEK/ERK [6,7]. Recent studies showed that miR-21 is frequently up-regulated in CRC and that elevated expression of miR-21 is associated with worse prognosis and inefficient response to chemotherapy [8,9]. Moreover, Li et al [10] found that knocking down miR-21 expression in the CRC cell line SW-480 suppressed the invasion, migration, and proliferation of the cells.…”
Section: Kolorektal Karsinoması Olan Hastalarda Xrcc1 Gen Polimorfizmmentioning
confidence: 99%